Expressão diferencial do gene FLA 14 em tegumento de sementes de soja - Monzón, Daisy Leticia Ramirez (2012)
The soybean (Glycine max L. Max) is one of the main crops grown in Brazil, the second largest world producer. Its evolution has been strongly supported by the development of technologies that allowed the acreage increase. Currently, the use of biotechnology tools aims to contribute to the development of new genotypes with characteristics that can continue increase the production. The identification of genes responsible for characters that can assist in developing varieties with improved seed quality may constitute something innovative. The seed tegument has an important function as for the seeds resistance to deterioration. In this sense, the partial characterization of the protein expression FLA 14 (Arabinogalactan), directly related to the cell wall synthesis in the seed tegument may contribute to the advancement of these studies. The aim of this work was to generate and validate primers capable of quantifying the gene expression of the FLA 14 protein in four soybean genotypes, two with black tegument (TP and IAC 222) and higher lignin content and two with yellow tegument (CD 202 and Potência) and lower lignin content. The plant tissue (tegument) was collected 50 days after the anthesis. In order to obtain the gene expression among genotypes, it was used the qRT-PCR technique, where it was tested four combinations of primers, constructed from sequence models of soybeans ESTs. With the validation results, the primers that were found within the standards were the FLA 14p1, FLA 14p2 and β-Actina. They were all used at the expression studies. The results of the relative expression showed that soybean genotypes with black tegument and higher lignin content express the FLA 14 protein quantitatively superior to the genotypes with yellow tegument and lower lignin content.